A Novel Trauma-Informed Screening Approach for Teen Dating Violence Perpetration in Racially Diverse Adolescents: A Multi-Site Study, Houston, Texas, and Champaign, Illinois, 2019-2021 - Cohen, Joseph R. ([Verlag nicht ermittelbar], 2024)
Teen dating violence (TDV) is an increasing criminal justice and public health issue. Due to these startling trends, federal agencies have called for increased prevention programming for this pattern of violence. In response, the proposed study tests whether a trauma-informed risk algorithm, based on modifiable risk and protective factors, can properly forecast TDV-perpetration risk in diverse adolescent samples. High school students in Texas (N=507) and adolescents participating in a juvenile diversion program in Illinois (N=77) completed surveys at baseline, 6-months, and 12-months. Surveys measured TDV-perpetration and other violent behavior, childhood adversities, individual risk factors for TDV-perpetration, and interpersonal and culturally-relevant protective factors. A novel analytic plan involving latent growth curve modeling and evidence-based medicine (EBM) was used to contextualize each risk factor's relation to TDV-perpetration and how these findings into an empirically-based decision-making tool.